A Novel Compact Ultra-Wideband Antenna with Hybrid IE3D/GA Optimization - Subbarao, A.; Sreedhar, K.; Raghavan, S.; Gayatri, N. (International Journal of Engineering and Technology, 2018)
A novel compact Ultra-wideband antenna is fabricated and measured. The antenna has a size of 31 mm x 34 mm. The antenna is excited by coplanar wave guide and it provides band width from 3.1 GHz to 10.6 GHz with dual notched bands of 3.3-4.2 GHz and 5.1-6 GHz to avoid interference from worldwide interoperability for microwave access and wireless local area network bands respectively in ultra-wideband. These dual notched band characteristics are obtained by etching a co-directional complementary split ring resonator on radiating patch of the antenna. The antenna dimensions and dual notched bands are optimized by hybrid Genetic Algorithm and IE3D electromagnetic solver. The measured antenna has Omni directional radiation pattern and consistent gain in operating frequency range.Â The time domain group delay of antenna is also measured, which indicates that the antenna has good pulse handling capacity. This antenna can be easily integrated with portable UWB systems.Â Â